Hemostatic efficiency of amphiphilic peptide solution in Wistar Rat model - Carter, Tiffany (Kansas State University, 2014)
One of the leading causes of death following traumatic injury is exsanguination. The body addresses bleeding through the process of hemostasis which includes the formation of a fibrin mesh structure that holds a blood clot together. During traumatic injury, hemostasis may be unable to stop excess bleeding. Fibrin based hemostatic agents have been developed, however, these studies often use fibrin obtained from biological sources, which poses risk of infection. A novel amphiphilic peptide (h9e) has been studied to form three dimensional nanofibers networks. In this research, we studied the ability to form a synthetically produced, fibrin-mimic, hemostatic material from the h9e peptide sequence. The objective of this study was to determine the blood gelation strength of the h9e peptide necessary to arrest bleeding in the Wistar Rat model. Commercial mouse blood was used for blood gelation in vitro studies. Dynamic rheometer was used to determine the gelation kinetics at varied h9e peptide concentrations ranging from 1-5% wt. By directly mixing the h9e peptide with blood, we observed that the blood gelation strength right after mixing increased as the h9e peptide weight % concentration increased, from 67 to 1086 Pascals in the peptide concentration from 1 to 5%, respectively. After 24 hours, final gelation strength of all concentrations with commercial mouse blood was lower than the instantaneous strength but consistent throughout testing. Similar testing was conducted using commercial Wistar Rat blood with weight % concentrations of 1, 3, and 5% of h9e peptide. The gelation strength was 500, 1665, and 1914 Pascals, respectively. We also determined the gelation strength of Wistar Rat blood components, such as red blood cells, serum, and plasma with 1% h9e peptide. We observed the gelation response induced with individual blood components; however, the strength is weaker than whole blood. In vivo, we applied the cut-tail method by dipping the cut-tail of Wistar Rats into the h9e peptide solutions for 10 seconds and then took it out for blood lost collection. We observed that h9e peptide solution at 1, 3, and 5% weight concentrations can all generate hemostatic function. The h9e peptide solution at 5% weight concentration (1914 Pa) was able to outperform a commercial hemostatic material (Moore Medical CELOX* Hemostatic Granules), significantly reducing both bleeding time and blood lost: h9e peptide at 5% had a bleeding time of 94 sec and 0.75 mL blood lost, while the Celox hemostatic granules had a bleeding time of 225 sec and 1.5 mL blood lost. Transmission Electron Microscopy and Spinning Disk Confocal Microscope imaging indicated a blood component reinforced, web-like, h9e nanofiber structure similar to the structure formed by fibrin in a blood clot. This study showed that h9e peptide has the potential to be used to induce hemostasis.
Keywords: h9e; Peptide; Amphiphilic; Hemostasis; Wsitar rat